Relationships of Cadmium, Lead, and Mercury Levels With Albuminuria in US Adults: Results From the National Health and Nutrition Examination Survey Database, 2009–2012. Issue 7 (15th March 2019) - Zhu, Xiu-Juan; Wang, Jing-Jing; Mao, Jian-Hua; Shu, Qiang; Du, Li-Zhong
Abstract: In this cross-sectional study, we evaluated associations between cadmium, lead, and mercury levels and the presence of albuminuria in US adults who participated in the National Health and Nutrition Examination Survey during the period 2009–2012. A total of 2, 926 adults aged ≥20 years were included, representing a population-based sample of 18, 264, 307 persons. Data on blood and urinary levels of cadmium, lead, and mercury and urinary albumin concentration (albuminuria, measured as albumin:creatinine ratio (ACR) ≥30 mg/g) were obtained. Multivariate linear regression was used to analyze associations between log-transformed cadmium, lead, and mercury levels and the presence of albuminuria. Urinary ACR was significantly higher among participants with a blood cadmium level of 0.349–0.692 μg/L (quartile 3) than in those with a blood cadmium level less than or equal to 0.243 μg/L (quartile 1) (crude β = 0.15, 95% confidence interval (CI): 0.01, 0.28). Participants with a urinary cadmium level greater than or equal to 0.220 μg/L had a significantly higher ACR (0.220–0.403 μg/L (quartile 3): crude β = 0.12 (95% CI: 0.03, 0.21); ≥0.404 μg/L (quartile 4): crude β = 0.29 (95% CI: 0.18, 0.39)) than those with a urinary cadmium level less than or equal to 0.126 μg/L (quartile 1). In conclusion, only blood and urinary cadmium levels, not mercury or lead levels, were associated with albuminuria among adults in this population.